Evaluation of Pneumothorax Recurrence in Patients with Spontaneous Pneumothorax Treated with Slurry Pleurodesis with Tetracycline - Mohsen Kolahdouzan; Sayed Mozaffar Hashemi; Simin Shokrollahi (مجله دانشکده پزشکی اصفهان, 2016)
Background: Spontaneous pneumothorax occurs without any predictable factor. This leads to accumulation of air in pleural cavity, which can cause dyspnea and in severe cases even death.